Shear wall construction in buildings: a conceptual framework on the aspect of analysis and design - Eusuf, Muhammad Abu; Abdur Rashid, Khairuddin; Mohd. Noor, Wira; Al Hasan, Abdullah (Trans Tech Publications Ltd., Switzerland, 2013)
This study describes the analysis and design process of shear wall construction, which is applied in various types of building construction. Shear walls resist lateral forces viz. earthquake force and wind force for high-rise structure and gravity load for all type of structure. Besides, Buildings with cast-in-situ reinforced concrete shear walls are widely used in earthquake-prone area and regions in the world. Research methods were confined to library research and employed software for analysis. The analytical accuracy of complex shear wall system have always been of concern to the civil and structural Engineering system. The software of this system is performed on the platform of modelling and then, the system models are usually idealized as line elements instead of continuum elements. Single walls are modelled as cantilevers and walls with openings are modelled as pier/ spandrel systems. In order to find the stiffness, the simple systems models can provide reasonable results. It has always been accepted that a scale based model in the FEM is exact and justifiable.